2015
DOI: 10.1371/journal.pone.0136154
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Deforestation and Land-Use Change Scenario Generator for Use in Climate Modelling Studies

Abstract: A new deforestation and land-use change scenario generator model (FOREST-SAGE) is presented that is designed to interface directly with dynamic vegetation models used in latest generation earth system models. The model requires a regional-scale scenario for aggregate land-use change that may be time-dependent, provided by observational studies or by regional land-use change/economic models for future projections. These land-use categories of the observations/economic model are first translated into equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Although over the last few years a big effort has been made in the modelling community to improve the representation of the biophysical and biogeochemical LCC climate impacts, an additional effort is still needed to overcome: (a) the apparent mismatch of scales at which LCC actually occur and those usually adopted in model experiments in ESMs (Rounsevell et al 2014, Tompkins et al 2015, (b) the different temporal and spatial scales of biophysical and biogeochemical processes and (c) the current oversimplified treatment of LCC in ESMs (Rounsevell et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although over the last few years a big effort has been made in the modelling community to improve the representation of the biophysical and biogeochemical LCC climate impacts, an additional effort is still needed to overcome: (a) the apparent mismatch of scales at which LCC actually occur and those usually adopted in model experiments in ESMs (Rounsevell et al 2014, Tompkins et al 2015, (b) the different temporal and spatial scales of biophysical and biogeochemical processes and (c) the current oversimplified treatment of LCC in ESMs (Rounsevell et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our review revealed many more road ecology publications from Africa than we expected, with a significant increase in the number of publications since 2006. Most of the publications were from the more affluent and politically stable regions (e.g., southern and East Africa), particularly pre-2006 publications (Drews, 1995;Dean and Milton, 2000), whilst post-2006 publications saw an increase in the number of papers from Central Africa (Hicks et al, 2012;Tompkins et al, 2015;Cameron et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Beginning with the least influential variable in the model's accuracy and skill, the next least influential variable is added, and additional variables sequentially added until only one variable, the most influential remains. This process informs the model development as it identifies those variables that did not significantly improve the overall accuracy of the model and can be permanently excluded [30,31]. The above sensitivity tests provide valuable information that the MLP use to generate the most parsimonious model.…”
Section: Model Development and Projectionsmentioning
confidence: 98%